Clinical Paternalistic Model and Problematic Situation: A Critical Evaluation of Clinical Counseling - Ahmad Sadati; Kamran Lankarani; Halimeh Enayat; Akbar Kazerooni; Sara Ebrahimzadeh (Shiraz University of Medical Sciences, 2014)
Background: Many of health system services are done in clinical counseling. A patient's expectation of clinical consultation and physician office visits is to obtain diagnostic-remedial results, while such an expectation can be fulfilled only through an active relationship between the doctor and the patient. The aim of this study is to evaluate the quality of doctor- patient interaction in an educational clinic in southern Iran. Methods: This is a conversation analysis based on critical approach. So, 33 clinical consultations were analyzed critically. Results: Results showed that paternalistic model is the overall pattern in consultations. This leads to limitation of the patients' opportunity to participate in their diagnosis and treatment. Powers' asymmetrical relations lead to conditions in which physicians determine the clinical counseling process. Also, physicians determine the subject of consultation in the counseling period. In this situation, the patients' concerns were ignored. This ignorance leads to the patients' suppression in problematic situations. The main point is that the clinical counseling occurs in one general contract that is unwritten but has been known for the two sides of interaction. Conclusion: Clinical counseling can be an active consultation when it included the symmetrical distribution of power and the patient has an active participation in the consultation. Therefore, the new patient-centered approaches can be an appropriate model for access to a type of consultation based on symmetrical power distribution between physician and patient.